Comparative Study of Two Semi-Occluded Vocal Tract Protocols: A Randomized Clinical Trial. - Heller-Stark, Amanda; Maxfield, Lynn; Herrick, Jennifer; Smith, Marshall; Titze, Ingo (Journal of Speech, Language & Hearing Research, 2024)
Introduction: Semi-occluded vocal tract exercises (SOVTEs) are widely used as a therapeutic tool to create flow resistance in the upper airway. The current study was a randomized controlled clinical trial to establish the efficacy of two SOVTE protocols, flow-resistant tube (FRT) and Lessac-Madsen Resonant Voice Therapy (LMRVT). Exploratory investigations included a noninferiority analysis of FRT to the widely adopted therapy protocol (LMRVT), as well as examining the dosing required to improve acoustic measures and subjective ratings. Method: Sixty-seven participants with voice disorder were randomized into one of five groups: 4-week FRT (n = 14), 8-week FRT (n = 19), 4-week LMRVT (n = 15), 8-week LMRVT (n = 5), and control (n = 14). Voice Handicap Index (VHI) and Vocal Fatigue Index scores were collected pre- and posttreatment. Acoustic analysis using the Acoustic Voice Quality Index was completed. We compared VHI between controls and 8-week FRT and LMRVT, adjusting for pre-VHI using linear regression. We examined the efficacy of 4-week protocols relative to controls and conducted a noninferiority comparison of FRT (4 and 8 weeks) to LMRVT (4 and 8 weeks) using 5- and 10-point margins. Finally, we compared the 4- versus 8-week sessions for both therapies. Results: A statistically significant reduction of VHI in both 8-week FRT relative to controls (-10.60, 95% CI [-19.80, -1.40], p = .025) and 8-week LMRVT (-15.74, 95% CI [-29.40, -2.08], p = .025) was found. We also found an improvement in 4-week FRT relative to controls (-10.11, 95% CI [-20.03, -0.20], p = .046), but the 4-week LMRVT result was not statistically significant (p = .057). FRT was found to be noninferior to LMRVT in terms of VHI using a 10-point margin (FRT - LMRVT: 0.69, 95% CI [-5.76, 7.15], p = .01), but not using a 5-point margin (p = .054). There were no statistically significant differences in VHI scores between 4- and 8-week sessions for either therapy. Conclusions: Both FRT and LMRVT improved VHI scores relative to controls. FRT was noninferior to LMRVT in terms of VHI scores. There were no statistically significant differences in VHI scores between 4- and 8-week therapy sessions.